2020
DOI: 10.1002/cctc.202000184
|View full text |Cite
|
Sign up to set email alerts
|

Retorting Photocorrosion and Enhanced Charge Carrier Separation at CdSe Nanocapsules by Chemically Synthesized TiO2 Shell for Photocatalytic Hydrogen Fuel Generation

Abstract: Metal chalcogenide‐based semiconductor nanostructures are promising candidates for photocatalytic or photoelectrocatalytic hydrogen generation. In order to protect CdSe from photocorrosion, a layer of TiO2 wrapped (shell) onto CdSe (core) nanocapsule via the post‐synthesis process. The morphology studies confirm that a thin crystalline TiO2 shell (3–8 nm) wrapped in all the three directions onto CdSe core and thickness of the shell can be controlled through modulating the titania precursor concentration. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…[34]. The similar type of functional nature of CuS/NiO heterostructures has been previously reported [35][36][37]. In general, the binding energy values obtained from XPS bands in this work are in good agreement with standard XPS binding energy values of Cu, S, Ni and O found in the previous reports [38].…”
Section: Structural and Surface Analysissupporting
confidence: 91%
“…[34]. The similar type of functional nature of CuS/NiO heterostructures has been previously reported [35][36][37]. In general, the binding energy values obtained from XPS bands in this work are in good agreement with standard XPS binding energy values of Cu, S, Ni and O found in the previous reports [38].…”
Section: Structural and Surface Analysissupporting
confidence: 91%
“…Meanwhile, the core peak at 133.2 eV of P 2p spectrum (Figure 7f) could be assigned to the binding energy of P 2p 3/2 , which is in good agreement with the earlier reports. 56,57 From the existing results, it is clearly seen that before and after incorporation of Cu 3 P, the peak positions of Cd and Se in the deconvoluted spectrum were not altered. This clearly implies that there is no peak shift.…”
Section: Resultsmentioning
confidence: 94%
“…The results showed that the formed sandwich‐like tandem heterostructure further inhibited their photocorrosion. [ 32 ] Owing to their intimate interfacial contact and matched band position, the photogenerated electrons of CdSe can transfer quickly to MoSe 2 nanosheets. On the other hand, the holes transfer to the other side to oxidize H 2 O to form O 2 , thus suppressing the backward reaction and photocorrosion.…”
Section: Resultsmentioning
confidence: 99%